Fine Mapping and Candidate Gene Analysis of BnC08.cds, a Recessive Gene Responsible for Sepal-Specific Chlorophyll-Deficiency in Brassica napus L. - Zhang, Wei; Zhou, Xiaoying; Chen, Feng; Zhu, Hongli; Shi, Rui; Sun, Chengming; Chen, Song; Hu, Maolong; Zhang, Jiefu; Wang, Xiaodong (Frontiers in Plant Science, 2022)
Chloroplast development is crucial for photosynthesis and plant growth and many factors are involved in its regulation. The regulatory mechanism differs in different green tissues and previous studies have focused on chloroplasts in leaves. In this study, a mutant with sepal-specific chlorophyll-deficiency was observed and named as df74. Genetic analysis indicated that the phenotype was controlled by a single recessive nuclear gene. The gene was located on chromosome C08 by bulked-segregant analysis with whole-genome sequencing, which was designated as BnC08.cds. To fine-map the BnC08.cds, a F2 population was created from the cross of df74 and Zhongshuang11. Finally, the BnC08.cds was fine-mapped in the region between the single-nucleotide polymorphism (SNP) markers M5 and M6, corresponding to a 228.72 kb interval of the B. napus ‘ZS11’ genome. Eighteen genes were predicted in the target region, and it was speculated that BnaC08G0442100ZS was the most likely candidate gene based on the results of transcriptome analyses and sequence variation analyses. These results provide a foundation to explore the regulation of chloroplast development in sepals.